PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE TAI (TEAMS ASSISTED INDIVIDUALIZATION) TERHADAP SIKAP KERJASAMA DAN SIKAP BERTANGGUNG JAWAB SISWA - Ishak, Muchamad (Jurnal Olahraga, 2015)
This study aims to reveal the effectiveness of the TAI type of cooperative learning model in enhancing students' attitude of cooperation and responsible attitude. The learning model emphasizes more on solving individual learning problems as a group's responsibility, so that the model is believed to improve cooperation and responsibility. The method used is an experimental method with a "randomized control group pretest-posttest design" design. The population that became the object of this study were all students of class X SMK PGRI 3 Cimahi totaling 120 people, samples were taken as many as 60 people randomly. Then the initial test is done as a reference to divide into two different groups, namely the TAI type cooperative model and the conventional model. The instrument used in the form of a questionnaire regarding the attitude of cooperation and attitude of responsibility. Data obtained from initial and final tests are then processed and analyzed using SPSS Serie 16 with stages: Normality Test (Kolmogorov-Smirnov), Homogeneity Test (Lavene statistical), Analysis of variance (Independent samples t-test). First, there is an effect of the type of TAI cooperative learning model on student cooperation attitude. Second, there is an influence of the TAI type cooperative learning model on students' responsible attitude. Third, there is an influence of conventional learning models on student cooperation attitude. Fourth, there is an influence of conventional learning models on students' responsible attitudes. and Fifth, the TAI type of cooperative learning model is better than the conventional model of cooperative attitudes and students' responsible attitudes.